Progress, Challenges, and Opportunities for 2D Material Based Photodetectors - Long, Mingsheng; Wang, Peng; Fang, Hehai; Hu, Weida (Advanced functional materials, 2019)
2D material based photodetectors have attracted many research projects due to their unique structures and excellent electronic and optoelectronic properties. These 2D materials, including semimetallic graphene, semiconducting black phosphorus, transition metal dichalcogenides, insulating hexagonal boron nitride, and their various heterostructures, show a wide distribution in bandgap values. To date, hundreds of photodetectors based on 2D materials have been reported. Here, a review of photodetectors based on 2D materials covering the detection spectrum from ultraviolet to infrared is presented. First, a brief insight into the detection mechanisms of 2D material photodetectors as well as introducing the figure‐of‐merits which are key factors for a reasonable comparison between different photodetectors is provided. Then, the recent progress on 2D material based photodetectors is reviewed. Particularly, the excellent performances such as broadband spectrum detection, ultrahigh photoresponsivity and sensitivity, fast response speed and high bandwidth, polarization‐sensitive detection are pointed out on the basis of the state‐of‐the‐art 2D photodetectors. Initial applications based on 2D material photodetectors are mentioned. Finally, an outlook is delivered, the challenges and future directions are discussed, and general advice for designing and realizing novel high‐performance photodetectors is given to provide a guideline for the future development of this fast‐developing field. Photodetectors based on 2D materials with excellence performance are demonstrated in recent years. The fast development of this field, including many important progresses such as ultrahigh photoresponsivities, room temperature long wavelength infrared photodetections, images by graphene array devices, and polarization sensitive photodetections, are reviewed. The large number of 2D materials give great opportunities to explore novel high‐performance photodetectors.